Impact of serum level concentrations of IgG and IgM on abortion in women who had both risk factors diabetes and hypertension: Impact of serum level concentrations of IgG and IgM on abortion - Khalid Khudhur, Pinar (Cellular and Molecular Biology, 2023)
Abortion is a significant global public health concern affecting millions of women each year. Factors such as maternal diabetes and hypertension have been recognized as major contributors to increased abortion risk. Immunoglobulins, specifically IgG and IgM, play crucial roles in pregnancy outcomes and have been studied extensively. This study aimed to assess the levels of Toxoplasma IgG and IgM in aborted women with and without diabetes or hypertension. This cross-sectional study examined 64 women who experienced Toxoplasma gondii-induced abortions at Erbil Maternity Teaching Hospital between January 2021 and May 2021. Their medical history, including diabetes and hypertension status, was collected through interviews. Blood samples were analyzed using VIDAS technology to measure serum IgG and IgM levels. The mean IgG and IgM antibody levels were compared between groups of women based on the number of abortions, diabetes status, and hypertension status. In women with a history of abortion, IgM antibody levels differed significantly among the five groups (P ≤ 0.01). While the average serum toxoplasma IgG concentration varied between diabetic and non-diabetic women, these differences were not significant (P>0.05). Conversely, there were highly significant differences in the concentration of serum toxoplasma IgM (P<0.01). Comparing women with and without hypertension, no significant differences were found in the mean concentrations of serum toxoplasma IgG and IgM (P > 0.05). The IgM antibody had a significant impact on the number of performed abortions, and these effects were also observed in abortion in women with diabetes.